Analysis of the in vitro adherence of Streptococcus mutans and Candida albicans - Barbieri,Dicler de Sant'Anna Vitor (2007)
The objective of the present study was to investigate the in vitro adherence capacity of Streptococcus mutans and Candida albicans. Adherence assays were conducted on dental surfaces and analyzed by scanning electron microscopy (SEM). Extracted human teeth were inoculated with Streptococcus mutans or Candida albicans and with both species simultaneously, and incubated at 37ºC for 21 days. Bacterial inocula had been obtained from saliva samples of children that had been colonized by both organisms. ATCC reference strains were used as controls. SEM analyses showed that the biofilm that covered the entire analyzed dental surface was more homogeneous inoculated with the two microorganisms simultaneously than with each species separately. In a second experiment, carried out with isolates that had shown the highest adherence the isolates were tested for adherence to high-density polyethylene substrates. The potentialization of the adherence capacity of Streptococcus mutans and Candida albicans when in association was confirmed.